2017
DOI: 10.1038/mp.2017.101
|View full text |Cite
|
Sign up to set email alerts
|

Genetic contributors to variation in alcohol consumption vary by race/ethnicity in a large multi-ethnic genome-wide association study

Abstract: Alcohol consumption is a complex trait determined by both genetic and environmental factors, and is correlated with the risk of alcohol use disorders. While a small number of genetic loci have been reported to be associated with variation in alcohol consumption, genetic factors are estimated to explain about half of the variance in alcohol consumption, suggesting that additional loci remain to be discovered. We conducted a genome-wide association study (GWAS) of alcohol consumption in the large Genetic Epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
121
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(142 citation statements)
references
References 62 publications
21
121
0
Order By: Relevance
“…In addition, two other regions in 4q23 were associated with AUDIT total score in the meta-analysis: one of the index SNPs was located in the ADH1C gene; however, conditional analysis of this region in UKB alone suggests that these multiple hits may in fact be tagging the rs1229984 signal. This region has been previously associated with alcohol consumption, AUD, and AUDIT scores (6,7,9,10) We also replicated the association between KLB ( Supplementary Table 12), on chromosome 4q14, and alcohol consumption (9,11,12); the index SNP rs11940694, which is located in the intron of KLB, was associated with AUDIT total score in the present study. Clump based pruning identified rs11940694 and rs4975012 as independent hits in the KLB region.…”
Section: Gwas Meta-analysis Of Audit Total Scoresupporting
confidence: 85%
See 3 more Smart Citations
“…In addition, two other regions in 4q23 were associated with AUDIT total score in the meta-analysis: one of the index SNPs was located in the ADH1C gene; however, conditional analysis of this region in UKB alone suggests that these multiple hits may in fact be tagging the rs1229984 signal. This region has been previously associated with alcohol consumption, AUD, and AUDIT scores (6,7,9,10) We also replicated the association between KLB ( Supplementary Table 12), on chromosome 4q14, and alcohol consumption (9,11,12); the index SNP rs11940694, which is located in the intron of KLB, was associated with AUDIT total score in the present study. Clump based pruning identified rs11940694 and rs4975012 as independent hits in the KLB region.…”
Section: Gwas Meta-analysis Of Audit Total Scoresupporting
confidence: 85%
“…Variants in this region were associated with AUDIT total score, AUDIT-C and AUDIT-P, demonstrating that alcohol metabolism is a risk factor for both alcohol consumption and problematic use. The second strongest signal, also associated with the three AUDIT phenotypes, is located in KLB, confirming the robust association of this gene with both alcohol consumption (9,11,12) in humans, and in mice (12). However, the biology of this locus could be more complex than previously described.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…A meta-analysis included >105,000 individuals of European ancestry revealed that rs11940694 in KLB gene is associated with alcohol intake [12] . Genetic factors of AC vary by race and ethnicity [13] ; thereby GWAS in different population are needed to reveal the genetic pattern of AC.…”
Section: Introductionmentioning
confidence: 99%